Cover Feature: Fluorescence Quenching‐based Assay for Measuring Golgi endo‐α‐Mannosidase (Chem. Asian J. 11/2019). Issue 11 (14th May 2019) - Sano, Kanae; Kuribara, Taiki; Ishii, Nozomi; Kuroiwa, Ayumi; Yoshihara, Toshitada; Tobita, Seiji; Totani, Kiichiro; Matsuo, Ichiro
Abstract : A novel tool for measuring Golgi endo‐α‐mannosidase : This glycosidase catalyzes an alternative deglucosylation process for N‐glycans and plays important roles in the post‐endoplasmic reticulum quality control pathway. Here, a FRET quenching‐based probe labeled with a reporter dye at the non‐reducing end and a quencher molecule at the reducing end is reported. This probe is hydrolyzed by the glycosidase, resulting in an increased fluorescence intensity. This assay method enables a simple, sensitive and quantitative detection of enzyme activity in complex systems without glucosidase inhibitor. More information can be found in the Full Paper by Ichiro Matsuo et al. onpage 1965 in Issue 11, 2019 (DOI:10.1002/asia.201900240 ).